Rethinking evidence: a multidisciplinary approach to the use of synthetic data in healthcare – part II (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The essay examines the role of synthetic data in clinical trials and health technology assessment, highlighting its epistemological, legal, and ethical implications. Moving beyond the dichotomy between real and virtual data, it seeks to affirm the full scientific and regulatory legitimacy of synthesization as a generative operation of evidence. Rethinking evidence: a multidisciplinary approach to the use of synthetic data in healthcare – Part IIThrough a multidisciplinary approach and the analysis of a clinical case study, the essay underscores the need for new legal grammar capable of governing the ongoing transformation, combining technological innovation with the protection of fundamental rights and the systemic coherence of the legal order.
Keywords: Synthetic data; Clinical trials; Health Technology Assessment (HTA); Artificial intelligence; Data protection